“I do want to stop, at least I think I do”: An international comparison of recovery from nonsuicidal self-injury among young people. - Kelada, L.; Hasking, Penelope; Melvin, G.; Whitlock, J.; Baetens, I. (SAGE Publications, 2017)
Phenomenological and cultural understandings of recovery from the perspective of individuals who engage in nonsuicidal self-injury (NSSI) are rare. The primary study objective was to understand similarities across three samples in (a) how young people define recovery from NSSI and (b) what they consider helpful approaches taken by parents and professionals to assist their recovery. Using a cross-national sample of young people (n = 98) from Australia (n = 48), Belgium (n = 25) and the United States (n = 25), we assessed their perspectives on NSSI. Consistent across all samples, young people defined recovery as no longer having the urge to self-injure when distressed, often displayed ambivalence about recovery, and reported it was helpful when parents and professionals were calm and understanding. Acceptance of recovery as a process involving relapses may need to be emphasized in NSSI treatment, to ease the pressure young people often place on themselves to stop the behavior outright.